Carbon storage in Larrea Divaricata and L. cuneifolia (Zygophyllaceae) in Drylands of Central-Western Argentina - Martinez Carretero, Eduardo Enrique (2007)
We studied total stored carbon - aboveground and underground - in Larrea divaricata and L. cuneifolia species, which are the dominant species and form extensive shrublands in both extensive geomorphological units in Mendoza: piedmont and lowlands (45,022 km2). In randomly distributed plots aboveground and underground biomass was assessed using the extractive method. Data on type and distribution of shrublands were obtained from the vegetation map; species cover from field records using the point-quadrat linear method; and biomass of leaves, stems, and roots from randomly distributed plots. Carbon density was calculated using the 0.5 standard factor. Total carbon storage in the two geomorphological units reached 8,237 Tg, of which 36.3% corresponded to L. divaricata and 63.7% to L. cuneifolia. Considering both species together and their distribution, the lowlands store around 98.1% of the carbon, and the piedmont about 1.9%.